Family, Friends and Teachers: Why Indigenous Students Stay at or Leave School - Howard, Damien (The Australian Journal of Indigenous Education, 2002)
This paper considers the comments made Indigenous adults returning to school about their earlier experiences at school. They were written by Indigenous people who have chosen to return to education in the Northern Territory after leaving school early. They reflect the variety of factors which contributed to their motivation to stay at school when younger, or to leave school early. Fifty-two (52) Indigenous students wrote comments on their earlier school experiences. They came from all around Australia and ranged in age from late teens to early forties. What they experienced at different places and at different times was remarkably similar. It would seem overt discrimination was more prominent in times past and has become more subtle in recent times.